MODELLING OF PEDAGOGICAL SYSTEM OF PURPOSEFUL FORMATION OF FUTURE PHILOLOGISTS’ PROFESSIONAL SUBJECTNESS - Арістова, Наталья Олександрівна (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2017)
The approaches of scientists to define the essence of concepts “system”, “pedagogical system”, “model” are analysed in the article. The different types of classifications of pedagogical systems are presented. The author theoretically grounds the model of pedagogical system of the purposeful formation of future philologists’ professional subjectness, which includes the following components: conceptual-and-propaedeutic, contensive-and procedural, resultative-and-evaluative and verificatory. The given pedagogical system of the purposeful formation of future philologists’ professional subjectness is an open, heterostatic and dynamic construct, which appears, formed and develops in the educational process of higher educational establishment.